2012
DOI: 10.1186/1752-0509-6-27
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic network analysis predicts efficacy of FDA-approved drugs targeting the causative agent of a neglected tropical disease

Abstract: BackgroundSystems biology holds promise as a new approach to drug target identification and drug discovery against neglected tropical diseases. Genome-scale metabolic reconstructions, assembled from annotated genomes and a vast array of bioinformatics/biochemical resources, provide a framework for the interrogation of human pathogens and serve as a platform for generation of future experimental hypotheses. In this article, with the application of selection criteria for both Leishmania major targets (e.g. in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Multiple in vitro studies suggested that disulfiram has a broad antipathogen potential. Upon screening of diverse chemical libraries, we and others reported the activity of disulfiram against intracellular amastigotes of L. donovani (17) and both parasite stages of L. major (18)(19)(20). Disulfiram also showed activity against Mycobacterium tuberculosis, Plasmodium falciparum, and Giardia lamblia (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple in vitro studies suggested that disulfiram has a broad antipathogen potential. Upon screening of diverse chemical libraries, we and others reported the activity of disulfiram against intracellular amastigotes of L. donovani (17) and both parasite stages of L. major (18)(19)(20). Disulfiram also showed activity against Mycobacterium tuberculosis, Plasmodium falciparum, and Giardia lamblia (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…It also has cytotoxic activity against some cancer cells (14-16). We and others have reported that disulfiram is active at nanomolar concentrations against intracellular amastigotes of L. donovani (17) and against L. major amastigotes (18) or promastigotes (19,20). Studies in BALB/c mice infected with L. major showed that administration of disulfiram at 160 mg/kg of resulted in significant reduction (50%) of the footpad lesion in comparison to sham-treated mice (19).…”
Section: This Novel Combination Of Thiuram Disulfides and Divalent Mementioning
confidence: 99%
See 1 more Smart Citation
“…Computational methods have been successfully applied in the drug discovery pipeline against a number of pathogens (108)(109)(110). Genes (and combinations of genes) that we identify to be important for in vivo survival can now be tested as potential new drug targets using existing drugs or KO strains in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Chavali et al (2012) have extensively reviewed the existing systems modeling approaches to drug discovery. Previously, Raman et al (2008) combined qualitative metabolic modeling with structural modeling to identify potential new druggable Mycobacterium tuberculosis targets.…”
Section: Introductionmentioning
confidence: 99%